(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Oncological rehabilitation plays a critical role in enhancing the quality of life and functional recovery of cancer survivors. In many local healthcare systems, especially in developing regions, rehabilitation remains an underprioritized component of comprehensive cancer care. Objective: This study aims to explore practical strategies to improve oncological rehabilitation services within local healthcare infrastructures by identifying existing gaps, evaluating current practices, and proposing sustainable interventions. Methods: A qualitative review of literature and analysis of local healthcare frameworks was conducted, focusing on patient access, interdisciplinary collaboration, availability of specialized staff, and integration of psycho-social support. Results: Findings indicate that oncological rehabilitation can be significantly improved through the development of regionally adapted rehabilitation protocols, enhanced training for medical personnel, investment in rehabilitation centers, and improved patient referral pathways. The involvement of multidisciplinary teams and digital health tools was found to increase rehabilitation effectiveness. Conclusion: Strengthening oncological rehabilitation within local healthcare systems requires a coordinated approach that includes policy reform, capacity building, and community-based support mechanisms. These enhancements can lead to better physical, psychological, and social outcomes for cancer survivors, ultimately reducing long-term healthcare burdens.